FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN GENERALIZED AUDIT SOFTWARE DI KAP - Yenni, Elsa Imelda (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study is to obtain empirical evidence about the Generalized Audit Software feature moderate the relationship between perceived ease of use and the use of Generalized Audit Software on external auditors in the Public Accountant Office for the period 2019. The research sample was obtained using the random purposive sampling method, namely 12 Offices Public Accountant. The model used in this study is a structural equation model and the data in this study were processed using SmartPLS version 3.0 for Windows. The results of this study indicate that perceived ease of use has no significant effect on the use of Generalized Audit Software, the complexity of Generalized Audit Software features has a significant effect on the use of Generalized Audit Software while the complexity of Generalized Audit Software features does not moderate the relationship of perceived ease of use and the use of Generalized Audit Software.